School as an educational context for the development of students’ social competence - Zukorlić, Mirsada; Nikolić, Ivko (Sociološki pregled, 2022)
The paper discusses the possibilities of developing the social competence of students at school using the method of theoretical analysis. The school is expected to adapt its way of working with students to new needs, in order to develop certain segments from a number of individual and social abilities as a capacity for social success – social competence. The school, with its educational mission, within which the role of teachers is crucial, encourages social competences through: acquiring and expanding students’ social knowledge and understanding of social reality; drawing students’ attention to other people’s feelings and interests; encouraging alternative interpretations of other people’s behaviour; providing students with assistance in active participation in discussions; assisting students in discovering common features; supporting communication between students (fostering verbal and nonverbal communication); encouraging the constructive cooperation among students; strengthening empathy and strengthening altruism).